Exhaustive Training Leads to Hepatic Fat Accumulation. Issue 8 (3rd March 2017) - da Rocha, Alisson L.; Pinto, Ana P.; Teixeira, Giovana R.; Pereira, Bruno C.; Oliveira, Luciana C.; Silva, Adriana C.; Morais, Gustavo P.; Cintra, Dennys E.; Pauli, José R.; da Silva, Adelino S. R.
Abstract : Recently, we demonstrated that an overtraining (OT) protocol for mice based on downhill running sessions increased the hepatic phosphorylation of 70‐kDa ribosomal protein S6 kinase 1 (S6K1; Thr389), a downstream target of the mammalian target of rapamycin complex 1 (mTORC1). In liver, the overactivation of the Akt/mTORC1 pathway induces lipogenesis via regulation of the action of sterol regulatory element binding protein‐1 (SREBP‐1) at multiple steps. Herein, we verified the effects of three running OT models with same external load (i.e., the product between intensity and volume of training), but performed in downhill, uphill and without inclination, on the proteins related to the mTORC1 signaling pathway, the protein content of the SREBP‐1, ACC, and FAS, and the morphological characteristics of C57BL/6 mouse livers. In summary, the downhill running‐induced OT model up‐regulated the levels of major proteins of the mTORC1 signaling pathway, the protein levels of SREBP‐1 (p125 precursor) and induced signs of cell swelling accompanied by acute inflammation. The other two OT protocols performed uphill and without inclination did not modulate the most analyzed molecular proteins, but induced hepatic morphological alterations, suggesting an acute pathological adaptation. The three OT models induced hepatic fat accumulation. J. Cell. Physiol. 232: 2094–2103, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The downhill running‐induced overtraining model increased the levels of major proteins of the mTOR signaling pathway in mouse livers despite high levels of pAMPK (Thr172). The three overtraining models increased the percentage of fat in liver.